Improving the account record management of a customer success management team: An insider action research - Roque, Jeremias P., Jr. (Animo Repository, 2023)
Effective account records management is vital to the success of customer success managers (CSMs) in software companies. It enables better customer service, proactive issue resolution, collaboration, and data-driven decision-making. This study contributes to the knowledge base on the relevance of knowledge and performance management in improving account records practices by implementing two action research cycles to address inconsistent, inaccurate, and outdated records. The first cycle focused on improving process guidelines and process cascade. In contrast, the second cycle integrated account records management into the company's performance management system. In addition, the ADKAR change management strategy was employed alongside force-field analysis and group dynamics concepts. They helped create awareness, impart knowledge and skills, and reinforce change for sustainability. The interventions improved account records' accuracy, consistency, and timeliness, with team members benefiting from clearer guidelines and better compliance with processes. Although the specifics of this study may be unique to the organization, the broader context of action research applies to many organizations grappling with similar issues of inconsistent or outdated records. However, while the study focuses on account records management, it requires further research on whether the strategies implemented can be generalized to other business processes, as the effectiveness of the strategies may depend on the nature of the process, the organizational structure, and the culture of the organization. Nonetheless, this study highlights the importance of effective account records management in driving customer success. Further, it underscores the need for ongoing improvement efforts in this aspect.